Ankara Traditional Religious Music Culture Icons - Güray, Cenk (Journal of Alevism-Bektashism Studies, 2013)
The city of Ankara had supplemented its importance in the Republic Era, with the historical background and the cultural diversity she is richened by. Comprehensive traditional music culture of Ankara is one of the outstanding indicators of this rich cultural heritage of the capital, depending on a city culture going back to 3,000 B.C. Various religious facilities aroused from this rich culture enabled the entrance of many religious symbols to religious and secular musical examples of Ankara. The reflection of this phenomena in the folk songs of the recent centuries resulted in the placement of İslamic signs inside of the prosperous musical and literary contexts of these compositions. These symbols both encounter effects from the various İslamic periods-divisions, especially Alevism and the natural impacts of pre-İslamic periods on Islamic rituals. Keeping the track of these symbols inside of the folk songs is a very effective way of tracing social choices of the Ankara community in different time periods. The aim of this study is to follow the religious symbols in the Ankara folk songs of the recent centuries to examine the connections of symbols with the social life. This way, a consistent idea for the construction of the future, consistent with the past of Ankara will be tried to be developed.
Keywords: Folk songs of Ankara; religious symbols; cycle; spiritual migration; household of Messenger Muhammed